2018
DOI: 10.1002/ajoc.201800392
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Diketopyrrolopyrrole Derivative and Its Applications for Organic Phototransistors

Abstract: A small molecular diketopyrrolopyrrole (DPP) derivative containing 2,4‐difluorinated phenyl groups, 3,6‐bis(5‐((E)‐2,4‐difluorostyryl)thiophen‐2‐yl)‐2,5‐bis(2‐ethylhexyl)‐2,5‐dihydropyrrolo[3,4‐c]pyrrole‐1,4‐dione (EHD2FV), was synthesized by a cross‐coupling reaction with 90% yield. The solid EHD2FV film exhibited a broad optical absorption up to 1000 nm, it featured a deep‐lying LUMO energy (4.49 eV). EHD2FV was employed as an electron acceptor (n‐type) for bulk heterojunction (BHJ) layers, which act as a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The combination of organic small molecule and polymer is another strategy to enhance the performance of OPTs . Lee et al.…”
Section: Recent Progress In Optsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of organic small molecule and polymer is another strategy to enhance the performance of OPTs . Lee et al.…”
Section: Recent Progress In Optsmentioning
confidence: 99%
“…As a result, the P3HT : EHD3FV (8 : 2 wt ratio) BHJ‐based OPT achieved the maximum R of about 256.6 mA W −1 , which was higher than that of pristine P3HT OPT device (198.7 mA W −1 ) with the light intensity of 9.6 μW cm −2 . Furthermore, Lee and co‐workers further designed the 2,4‐difluorinated DPP derivative (EHD2FV) to explore the effect of dipole direction on molecular properties . The optimal OPT based on a P3HT : EHD2FV BHJ layer exhibited the best photosensing performance ( R ) of 337.1 mA W −1 at the EHD2FV molar ratio of 0.05 under the illumination of a deep red light.…”
Section: Recent Progress In Optsmentioning
confidence: 99%
“…In this study, it is demonstrated that the OFETs with n-type conjugated polymer channel layers, which could not be operated at low voltages in the dark condition, can work in an n-channel transistor mode due to the photogenerated charge carriers by the illumination of blue and deep-red light. Poly[{5, 5,11,11-tetrakis(5-(2-ethylhexyl) [3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone}] (PIDTT-NDI) was introduced as an n-type polymer in the present devices that do not work as a transistor at the low voltages less than 5 V in the dark condition (note that the PIDTT-NDI polymer exhibited typical n-channel transistor behavior at 10 V operation in our previous work 37 ). When two individual monochromatic light with a wavelength (λ) of 434 and 754 nm were illuminated, the devices with the PIDTT-NDI layers exhibited typical nchannel transistor behaviors at ≤5 V. The electrical conductance of devices was gradually increased with the incident light intensity, while the photosensitivity was greatly enhanced up to 14,000% at λ = 434 nm owing to the extremely low drain current level in the dark (5 V).…”
Section: Introductionmentioning
confidence: 99%
“…Organic field-effect transistors (OFETs) have attracted keen attention for the last three decades because OFETs have various advantages over conventional inorganic FETs in terms of low-temperature solution processes, flexible and foldable shapes, semitransparency, and so forth. However, the charge carrier mobility of OFETs is still far behind that of inorganic FETs even though the state-of-the-art studies have shortly reported considerably high mobilities of ca. 10–20 cm 2 /V .…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] This thin heterojunction, consisting of electron donor and acceptor, either blended to form the bulk heterojunction or deposited sequentially to form the planar heterojunction, provides the energy offsets of the photoactive junction for effective separation of bonded excitons. [5,[20][21][22][23][24][25][26][27] The interfacial charge effect between the separation, transport, and recombination is crucial for high photoresponse of organic phototransistors. Fullerene derivatives are dominantly selected as the electron acceptors, while many electron donors are available for photodetection layer assembling.…”
Section: Introductionmentioning
confidence: 99%